PENGARUH BIO SOLID 17 BERBASIS POME TERHADAP PH, KAPASITAS TUKAR KATION, DAN KAPASITAS MENAHAN AIR TANAH INCEPTISOL - Galang Indra Jaya; Guruh Sri Pamungkas; Sri Gunawan; Herry Wirianata; Idum Satia Santi; Adhy Ardiyanto; Agung Kurniawan; Yovi Avianto; Arief Panca Putra; Novan Pramana Aji (Jurnal Penelitian Pertanian Terapan, 2025)
Inceptisols are widely distributed in tropical regions, including Indonesia, and are characterized by high rainfall and intensive weathering. These conditions promote severe nutrient leaching, low cation exchange capacity (CEC), and moderately to slightly acidic soil pH, thereby limiting nutrient availability, fertilizer-use efficiency, and crop productivity, particularly in oil palm (Elaeis guineensis) plantations. This study aimed to evaluate the effects of BIO SOLID 17, an organic soil conditioner derived from palm oil mill effluent (POME) sludge, on the chemical and physical properties of Inceptisol through a controlled incubation experiment. A two-month laboratory incubation was conducted using a randomized complete block design with five application rates of BIO SOLID 17 (0, 5, 10, 15, and 20 kg ha⁻¹), each with five replications. Observed parameters included soil pH, cation exchange capacity (CEC), and water-holding capacity (WHC), which were analyzed using standard methods. The results demonstrated that BIO SOLID 17 application significantly improved Inceptisol soil quality in a dose-dependent manner. Soil pH increased from strongly acidic conditions (4.85) in the control to near-neutral levels (6.19) at the highest application rate. Soil CEC also increased significantly from 34.41 to 47.49 cmolc kg⁻¹, indicating enhanced nutrient retention capacity. In addition, soil water-holding capacity increased from 46.82% to 55.81%, reflecting improvements in soil aggregation and moisture retention. Overall, BIO SOLID 17 shows strong potential as a sustainable organic soil amendment for improving the chemical and physical fertility of Inceptisol. The utilization of POME-based materials supports circular economy principles by converting agro-industrial waste into value-added agricultural inputs. Further field-scale studies are recommended to confirm effectiveness and determine optimal application rates under oil palm plantation systems.